FORMULATION AND ACTIVITY TESTING OF RED ALGAE (Eucheuma cottonii) EXTRACT GEL AGAINST THE BACTERIA Propionibacterium acnes - Nurhikma Awaluddin; Andi Meinar Dwi Rantisari Thayeb; Andi Ulfiana Utari; Akbar Awaluddin; Nur Pebrianti Caronge (Jurnal Penelitian Pendidikan IPA, 2023)
Flavanoids are one of the many compounds in phenols that can denature bacterial cell membrane proteins, thus inhibiting cell growth. The purpose of this study was to formulate an anti-acne gel for the ethanolic extract of red algae (Eucheuma cottonii) and to test its antimicrobial activity against Propionibacterium acnes. The method used is laboratory research design by making antiacne gel preparations of red algae extract with concentrations of 1%, 3%, 5% and testing the antimicrobial activity with the agar diffusion method using wells on MHA media which is incubated for 1x24 hours. The results of the evaluation of the gel preparation before and after the cycling test met the requirements of organoleptic, homogeneity, pH, viscosity, and dispersibility where each formula was stable in the gel preparation. The results showed that red algae extract (Eucheuma cottonii) could be formulated and was stable in the form of an anti-acne gel and had antibacterial activity. In formula I with a concentration of 1% the inhibition zone formed was 36.33 mm, in formula II with a concentration of 3% the inhibition zone formed was 38.79 mm and in formula III with a concentration of 5% the inhibition zone formed was 34.27 mm. So which has optimal antibacterial activity against Propionibacterium acnes is formula II with a concentration of 3% and an area of ​​inhibition zone of 38.79 mm.